Механизмы расселения серой жабы (Bufo bufo (L. 1758); Amphibia, Anura) и особенности ее популяций в недавно заселенных местообитаниях - Маро, А.Н.; Шабанов, Д.А. (Матеріали Першої конференції Українського Герпетологічного Товариства, 2005)
This work is devoted to the studies of common toad Bufo bufo (Linnaeus, 1758) artificial moving to new habitats consequences that was performed in Kharkov region in 1994. The natural dispersion of toads has been found to occur in two ways. The first way includes a transfer of tadpoles with water. The second way includes incoming of toads into the reservoirs located between a former place of spawning and a ground habitat of toads settled by toads upon their metamorphosis. The new founded groups of breeding (local populations) differ from their progenitor groups with the substantially smaller size of males and bigger size of females. It seems that on settling of new habitats, common toad males tend to accelerate their maturing, while females tend to accelerate their growth.
Keywords: Bufo bufo; Популяции; Расселение; Стратегии